Adventures of Gallant Bess - Landers, Lew, 1901-1962; Rapf, Matthew, 1920-1991; Mitchell, Cameron, 1918-1994; Crestview Productions, Inc.; Cinetel ([United States] : Crestview Productions, 1948)
Ted Daniels, a ranch hand working for a rodeo, captures a magnificent wild horse that he tames and trains. As Ted is recovering from an accident that happened during a rodeo, the rodeo owner cheats him out of his horse. Ted must decide whether to pursue him and try to recover the horse, or whether to settle down with the doctor's daughter who is nursing him back to health. --
Originally released as a motion picture in1948.
With Gallant Bess, the wonder horse.
Cameron Mitchell, Audrey Long, Fuzzy Knight, James Millican, John Harmon, Ed Gargan, Harry V. Cheshire, Cliff Clark, EEvylynn Eaton.
Cinematographer, William Bradford; editor, Harry Komer; music, Irving Gertz.
Dubbed into Spanish; subtitles or closed captioned
Online resource; title from opening/closing credits (Digitalia Film Library, viewed September 18, 2015).
Keywords: Gallant Bess (Horse) -- Drama; Rodeos -- Drama; Horses -- Drama; Western films; Feature films; Internet videos; Streaming video